A Comprehensive Literature Review of Effect of Mineralocorticoid Receptor Blockers on Chronic Kidney Disease - Erick Persson Jeffry; Charles Sanjaya Seikka (The Indonesian Journal of General Medicine, 2025)
Background: The literature surrounding the effects of mineralocorticoid receptor blockers on chronic kidney disease (CKD) has evolved significantly over recent years, reflecting a growing understanding of their potential benefits and risks.  Literature Review: (Yanai et al., 2021) reinforced the cardiovascular protective effects of MRAs through their systematic review and meta-analysis, indicating that MRAs could significantly reduce cardiovascular events in CKD patients. In a similar vein, (B. Wish & Pergola, 2022) discussed the advantages of combining MRAs with ACE inhibitors or ARBs, while cautioning against the elevated risk of hyperkalemia. (Hu et al., 2023) provided a meta-analysis focusing on eplerenone, a selective MRA, suggesting its role as an adjunct therapy in CKD management, although they noted the need for further exploration of its safety profile. (Hedlund Møller et al., 2024) examined the paradoxical nature of MRA treatment, where increased hyperkalemia incidence was associated with decreased mortality risk, underscoring the need for a balanced approach in clinical decision-making. This duality illustrates the necessity of vigilant monitoring and patient management strategies to optimize the therapeutic benefits of MRAs while minimizing risks. Conclusion: In conclusion, the collective findings from these studies indicate that MRAs hold significant promise in the management of CKD, particularly in reducing proteinuria and offering cardiovascular protection. However, the associated risk of hyperkalemia poses a critical barrier to their widespread use. Future research is essential to further elucidate the long-term outcomes of MRA therapy, explore novel agents that separate organ protection from adverse effects, and establish guidelines that can enhance patient safety while maximizing therapeutic benefits.